2018
DOI: 10.3390/en11041001
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study on the Effectiveness of Grouting Reinforcement on the Large Heaving Floor of the Deep Retained Goaf-Side Gateroad: A Case Study in China

Abstract: Abstract:To study the effectiveness of grouting reinforcement on a large heaving floor of the retained goaf-side gateroad (RGSG) at a 900 m depth in the Zhuji coal mine, a numerical model involving strain softening constitutive material was built. First, the simulated deformations of the RGSG were compared with field data to verify the reliability of the numerical model. Then, the dynamic distribution of the stress in the RGSG floor was examined to reveal the mechanism of floor heave. Finally, grouting reinfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 23 publications
(23 reference statements)
0
14
0
Order By: Relevance
“…e control methods of floor heave in different situations are also different [24,25]. Zhang et al proposed the grouting reinforcement method for the large floor heave of the retained goaf-side gate road [26]. Wang et al analyzed the influencing factors of the floor heave of the roadways in the fault-fractured zone, including the influence of the faultfractured zone, the poor quality of floor rock masses, the deterioration of soaked floors, and weak floor supports.…”
Section: Introductionmentioning
confidence: 99%
“…e control methods of floor heave in different situations are also different [24,25]. Zhang et al proposed the grouting reinforcement method for the large floor heave of the retained goaf-side gate road [26]. Wang et al analyzed the influencing factors of the floor heave of the roadways in the fault-fractured zone, including the influence of the faultfractured zone, the poor quality of floor rock masses, the deterioration of soaked floors, and weak floor supports.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, in an attempt to establish a theoretical model of grouting, researchers have developed the spherical diffusion theory, cylindrical diffusion theory, carol theory, Baker formula, and G. Lombardi formula, among others Xiao et al 2019;Chen et al 2014;Zhu et al2019;Zheng and Zhang 2015). A large number of engineering studies have reported that the splitting grouting process is very complicated and is the result of uid-solid coupling between the seepage eld and stress eld (Zhang and Shimada 2018;Ra and Stille 2014;Wang 2019;Zhang et al 2017;Liu and Sun 2019;Sha 2019). The diffusion form of grout in coal seam cracks is di cult to obtain through laboratory tests or eld measurements.…”
Section: Introductionmentioning
confidence: 99%
“…In Guo et al study [13], in order to propose highly efficient and economical methods of controlling floor heave, numerical simulation, laboratory physical simulation, and engineering practice were carried out to reveal the mechanism of reinforcing roof and sidewalls to control the floor heave of the mining roadway, and engineering practice showed that the floor heave in the roadway, the roof, and the sidewalls, which was reinforced by intensive bolts combined with steel belt, wire mesh, and cable, was significantly reduced compared with that with lower supporting intensity of roof and sidewalls. In Zhang et al study [14], the dynamic distribution of the stress in the RGSG floor was examined to reveal the mechanism of floor heave. Finally, grouting reinforcement was proposed to control the RGSG floor, and the corresponding effectiveness was verified by improving the rock mechanics of the floor strata based on the results of numerical uniaxial compressive tests.…”
Section: Introductionmentioning
confidence: 99%